Hookah Smoking Profiles of University Students and Their Perceptions of its Health Risks - Çevik, Betül Esra; Kocataş, Semra (Addicta: The Turkish Journal on Addictions, 2020)
This study was conducted to determine the hookah smoking profiles among university students and their perceptions of the health effects of hookah. The stratified random sampling method was used, and each school was accepted as a layer. The number of students to be included in the sample from each class was determined by dividing the total number of students to be taken from the school by the number of classes in that school. After determining the number of students who would be taken from each class, the students to be included in the sample were selected from the student lists using a simple random sampling method. The sample of this study included 625 students from a university. The data collection tools were (a) a personal information form containing the sociodemographic characteristics of the students, the characteristics of smoking and hookah smoking behavior, and (b) the perception scale of the effects of hookah use on health. The data were collected by the researchers between February 5 and May 5, 2018, by distributing the questionnaires and scale forms to the students in the classroom environment and having them fill the forms. The data obtained were evaluated in the Statistical Package for the Social Sciences 22.0 program using chi-square, significance test of the difference between the 2 means, variance analysis, Mann–Whitney U test, Kruskal–Wallis H test, and logistic regression analysis. In this study, it was found that the frequency of hookah use was 65.2% in male students and 34.8% in female students, and the mean score of the students from the perception scale of the effects of hookah use on health was 60.83±9.96. The mean score of the students who do not smoke hookah (62.53±9.70) was higher than that of those who smoke hookah (57.45±9.83), and the difference between them was statistically significant (p
Keywords: Hookah; university students; nursing; health perception